Epistemology, Ethics, and Meaning in Unusually Personal Scholarship - Esping, Amber (Springer International Publishing, 2018)
This book uses Viktor Frankl's Existential Psychology (logotherapy) to explore the ways some professors use unusually personal scholarship to discover meaning in personal adversity. A psychiatrist imprisoned for three years in Nazi concentration camps, Frankl believed the search for meaning is a powerful motivator, and that its discovery can be profoundly therapeutic. Part I begins with four stories of professors finding meaning. Using the case studies as a foundation, Part II investigates issues of epistemology and ethics in unusually personal research from an existential perspective. The book offers advice for graduate students and faculty who want to live and work more meaningfully in the academy.